Fractal-Based Radiomic Approach to Tailor the Chemotherapy Treatment in Rectal Cancer: A Generating Hypothesis Study - Di Dio, Carmela; Chiloiro, Giuditta; Cusumano, Davide; Catucci, Francesco; Boldrini, Luca; Romano, Angela; Meldolesi, Elisa; Marazzi, Fabio; Corvari, Barbara; Barbaro, Brunella; Manfredi, Riccardo; Valentini, Vincenzo; et al. (Frontiers in Oncology, 2021)
Introduction Aim of this study is to create a radiomic model able to calculate the probability of 5-years Disease Free Survival (5yDFS) when Oxaliplatin (OXA) is or not administered in patients with locally advanced rectal cancer (LARC) and treated with neoadjuvant chemoradiotherapy (nCRT), allowing physicians to choose the best chemotherapy (CT) regimen. Methods LARC patients with cT3-4 cN0 or cT1-4 cN1-2 were treated according to an nCRT protocol that included concomitant CT schedules with or without OXA and radiotherapy dose of 55 Gy in 25 fractions. Radiomic analysis was performed on the T2-weighted Magnetic Resonance (MR) images acquired during the initial tumor staging. Statistical analysis was performed separately for the cohort of patients treated with and without OXA, respectively. The ability of each single radiomic feature in predicting 5yDFS as a univariate analysis was assessed using the Wilcoxon Mann Whitney (WMW) test or t-test. Two logistic models (one for each cohort) were calculated, and their performance was assessed using the area under the Receiver Operating Characteristic (ROC) curve (AUC). Results A total of 176 image features belonging to four families (morphological, statistical, textural and fractal) were calculated for each patient. At univariate analysis the only feature showing significance in predicting 5yDFS was the maximum fractal dimension of the subpopulation identified considering 30% and 50% as threshold levels (maxFD3050). Once the models were developed using this feature, an AUC of 0.67 (0.57-0.77) and 0.75 (0.56-0.95) was obtained for patients treated with and without OXA, respectively. A maxFD30-50 >1.6 was correlated to an higher 5yDFS probability in patients treated with OXA. Conclusion This study suggests that radiomic analysis of MR T2-w images can be used to define the optimal concomitant CT regimen for stage III LARC cancer patients. In particular, by providing an indication of the GTV spatial heterogeneity at initial staging, maxFD3050 seems to be able to predict the probability of 5yDFS. New studies including a larger cohort of patients and external validation sets are recommended to verity the results of this generating-hypotheses study